1993
DOI: 10.1038/bjc.1993.207
|View full text |Cite
|
Sign up to set email alerts
|

Activity of type IV collagenases in benign and malignant breast disease

Abstract: Using zymography and computer assisted image analysis, we have measured the levels of type IV collagenases in biopsies from normal breast, and benign and malignant breast disease. The 92 kDa form was present in three of 11 cases of normal/benign disease, three of nine grade I tumours, four of 12 grade II tumours, but 11 of 11 grade III tumours. Mean levels were higher in grade III tumours (P < 0.0001). When the levels of 72 kDa collagenase and its active 62 kDa form were considered together, there was no diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
155
4
8

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(185 citation statements)
references
References 22 publications
17
155
4
8
Order By: Relevance
“…Furthermore, in line with several studies suggesting stromal macrophages and tumour-infiltrating neutrophils as major sources of MMP-9 in invasive cancers, e.g. in colon (Nielsen et al, 1996;Pyke et al, 1993), breast (Davies et al, 1993a), and bladder cancer (Davies et al, 1993b) and in ovarian carcinoma (Naylor et al, 1994), we detected MMP-9 immunoreactivity in neutrophils and monocyte-macrophage-like cells both in stromal and epithelial areas. This is in contrast to the findings of Huang et al (2000), who recently demonstrated MMP-9 mRNA and protein both in stromal and neoplastic cells of ovarian carcinomas (Huang et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in line with several studies suggesting stromal macrophages and tumour-infiltrating neutrophils as major sources of MMP-9 in invasive cancers, e.g. in colon (Nielsen et al, 1996;Pyke et al, 1993), breast (Davies et al, 1993a), and bladder cancer (Davies et al, 1993b) and in ovarian carcinoma (Naylor et al, 1994), we detected MMP-9 immunoreactivity in neutrophils and monocyte-macrophage-like cells both in stromal and epithelial areas. This is in contrast to the findings of Huang et al (2000), who recently demonstrated MMP-9 mRNA and protein both in stromal and neoplastic cells of ovarian carcinomas (Huang et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…MMP-2 and MMP-9 are thought to play a role in the degradation of basement membrane collagen IV and, hence, may contribute to the invasive ability of breast cancer cells (Bae et al, 1993). In situ hybridization studies have shown that the expression of MMP-2 mRNA is mostly localized in the tumor fibroblasts, while MMP-9 mRNA was found to be expressed by epithelial cells and macrophages (Davies et al, 1993;Polette et al, 1993;Wilhelm et al, 1989;Poulsom et al, 1992;Fridman et al, 1995;Okada et al, 1995). Thus, several cellular constituents of the tumor may interact to carry out degradation of the extracellular matrix by modulating MMP expression.…”
mentioning
confidence: 99%
“…Two members of the MMP family, the 72-kDa (MMP-2, gelatinase A) and 92-kDa (MMP-9, gelatinase B) proteinases, have been shown to be highly expressed in breast tumors in both the stroma and the cancer cells (Monteagudo et al, 1990;Davies et al, 1993;Sato and Seiki, 1993). MMP-2 and MMP-9 are thought to play a role in the degradation of basement membrane collagen IV and, hence, may contribute to the invasive ability of breast cancer cells (Bae et al, 1993).…”
mentioning
confidence: 99%
“…The results of this trial will be reported in the future. Type IV collagenase, matrix metalloproteinase (MMP) 2, and MMP 9, which are secreted by cancer cells, have been shown to play an important role in the degradation of BM (25)(26)(27)(28)(29). Expression of these enzymes by cancer cells has been found to be correlated with the malignant potential of various cancers (30 -36).…”
Section: Bm Preservationmentioning
confidence: 99%